2021
DOI: 10.1097/md.0000000000026033
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C infection and acute coronary syndrome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In another study, Butt et al reported that despite the presence of favorable lipid profile in patients infected with HCV, HCV infection was associated with greater risk of coronary artery disease with a hazard ratio of 1.27 (95% CI, 1.22-1.31) after adjustment of conventional risk factors [109]. Interestingly, a recent case-control study found contradicting results, in which there was no statistically significant association between HCV infection and acute coronary syndrome in the study population [110]. Several studies have examined the potential association between HCV infection and cerebrovascular events.…”
Section: Accelerated Atherosclerosismentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, Butt et al reported that despite the presence of favorable lipid profile in patients infected with HCV, HCV infection was associated with greater risk of coronary artery disease with a hazard ratio of 1.27 (95% CI, 1.22-1.31) after adjustment of conventional risk factors [109]. Interestingly, a recent case-control study found contradicting results, in which there was no statistically significant association between HCV infection and acute coronary syndrome in the study population [110]. Several studies have examined the potential association between HCV infection and cerebrovascular events.…”
Section: Accelerated Atherosclerosismentioning
confidence: 94%
“…Wu et al [110], 2021 Acute coronary syndrome There was no statistically significant correlation between HCV infection and hospitalization for acute coronary syndrome.…”
Section: Morales Et Al [76] 2016mentioning
confidence: 95%
“…Данные о роли других заболеваний печени, прежде всего хронического вирусного гепатита В и С, в развитии коронарного атеросклероза и ОКС неоднозначны. Некоторые авторы не выявили повышенного риска развития ИМ у пациентов с HCV-инфекцией [32,33], однако в другом исследовании HCV-инфекция сопровождалась значительным увеличением риска ИМ 2 типа (скорректированное отношение рисков 1,46, 95% ДИ 1,09-1,97), но не ИМ 1 типа [34]. По данным анализа 686 HCV-позитивных пациентов, вирусная инфекция оказалась независимым предиктором ангиографически подтвержденного поражения коронарных артерий (скорректированное ОШ 4,2; 95% ДИ 1,4-13,0) [35].…”
Section: материалы и методыunclassified
“…This effect was hypothesized when HCV + was found to be associated with the presence of CAD, which remained significant even after correction for cardiometabolic risk factors, and which was associated with the severity of disease (number of diseased vessels) [134]. Many further investigations have confirmed this link, whereas others have found no significant relationship [135][136][137]. As a result, the balance of these data ranges widely from no correlation to a favorable relationship.…”
Section: Potential Mechanisms Linking Hcv To Atherosclerosismentioning
confidence: 99%